2021
DOI: 10.1007/s11948-021-00293-x
|View full text |Cite
|
Sign up to set email alerts
|

Research and Practice of AI Ethics: A Case Study Approach Juxtaposing Academic Discourse with Organisational Reality

Abstract: This study investigates the ethical use of Big Data and Artificial Intelligence (AI) technologies (BD + AI)—using an empirical approach. The paper categorises the current literature and presents a multi-case study of 'on-the-ground' ethical issues that uses qualitative tools to analyse findings from ten targeted case-studies from a range of domains. The analysis coalesces identified singular ethical issues, (from the literature), into clusters to offer a comparison with the proposed classification in the liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…AstraZeneca's ethics principles aim to help employees and partners navigate the risks associated with AI systems. Yet principles alone cannot ensure that such systems are designed and used ethically (Mittelstadt, 2019), and their implementation is never straightforward (Ryan et al, 2021). Moreover, like many other multinational corporations, AstraZeneca is a decentralized organization.…”
Section: Case Study-astrazeneca's Ai Governance Journeymentioning
confidence: 99%
“…AstraZeneca's ethics principles aim to help employees and partners navigate the risks associated with AI systems. Yet principles alone cannot ensure that such systems are designed and used ethically (Mittelstadt, 2019), and their implementation is never straightforward (Ryan et al, 2021). Moreover, like many other multinational corporations, AstraZeneca is a decentralized organization.…”
Section: Case Study-astrazeneca's Ai Governance Journeymentioning
confidence: 99%
“…Furthermore, the data collected from farms can raise concerns about data ownership i.e., who owns the farm data and who has control over the use of farm data (Mark, 2019). This can lead to a power imbalance between farmers and technology or service providers (Ryan et al, 2021a). Accountability is another issue when it comes to AI-technologies; for instance, if AI systems spray substantial amounts of water or pesticides due to errors in the system, who will be responsible for the loss of harvest?…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified and discussed ethical issues that arise from AI and Big Data either on a normative or empirical level (Jobin et al, 2019;Müller, 2020;Ryan et al, 2021;Stahl et al, 2021). What is missing from existing literature however, is a comprehensive understanding of and engagement with, the challenges that arise when such attempts are made to mitigate the risks of Big Data and AI while ensuring that they are harnessed for the benefit and well-being of society.…”
Section: Introductionmentioning
confidence: 99%